Non Hodgkins Lymphoma Presenting with Urticarial Vasculitis - A Rare Association - Puri, N; Malhotra, SK (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Urticarial vasculitis (UV) has been described as a rare association with hematological malignancy. We report the case of a 52 year old patients of localized B-cell non- Hodgkin’s lymphoma who presented with a recurrent nonpainful urticarial type rash distributed around his face, arms, forearms, buttocks and lower legs since 1 year. The patient was managed by intensive combination chemotherapy (CHOP) regime for several cycles. The patient showed good response to treatment. The case is being reported because of the rare association of Non Hodgkin’s lymphoma with urticarial vasculitis. Key Words: Lymphoma; lymphadenopathy; chemotherapy; bone marrow; lymphoid; cutaneous; histology. DOI: 10.3329/jbsp.v29i1.7170 J Bangladesh Coll Phys Surg 2011; 29:41-43